ANALISIS PENGELOLAAN MODAL KERJA DAN AKTIVA TETAP DALAM MENINGKATKAN PROFITABILITAS PADA PT. KIMIA FARMA (PERSERO) TBK - Siti Nurul Islamiati; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research was conducted at PT. Kimia Farma (Persero) Tbk with the problem in this research is the decline in the company's ability to obtain profitability. The purpose of this study is to analyze the management of working capital and fixed assets in increasing profitability. Types and sources of data used are secondary and primer data which are derived from the financial statements of PT. Kimia Farma (Persero) Tbk for the period 2014-2018. Data collection techniques using the documentation in the form of financial statements and do interview, and while the data analysis technique used  in this study is ratio analysis.            The results showed that PT. Kimia Farma (Persero) Tbk as a whole has not been able to obtain working capital effectively, so it has an impact on the acquisition of profits that are not optimal, as well as with fixed assets, although the assessment through industry standards shows effective, but the impact given to profits is not too large, as evidenced by ineffective profitability ratios.Keywords: Working Capital, Fixed Assets, Profitability.